Spectroscopic Ellipsometry Investigation of Au‐Assisted Exfoliated Large‐Area Single‐Crystalline Monolayer MoS2. Issue 11 (18th September 2021) - Zou, Bo; Wu, Zuoxu; Zhou, Yu; Zhou, Yan; Wang, Jian; Zhang, Lianghui; Cao, Feng; Sun, Huarui
Abstract : The recent Au‐assisted mechanical exfoliation technique has enabled scalable fabrication of millimeter‐sized, high‐quality monolayer 2D crystals. Herein, spectroscopic ellipsometry characterization of as‐exfoliated single‐crystalline monolayer MoS2 is reported. By developing layer‐by‐layer ellipsometry measurements and analysis, the complex dielectric function of monolayer MoS2 is extracted. Compared with bulk MoS2, the A and B exciton peaks in the dielectric function spectrum nearly disappear in the 1L MoS2 –Au hybrid system. The charge transfer at the 1L MoS2 –Au interface is responsible for this observation and the conclusion is also supported by Raman, photoluminescence, and differential reflectance measurements. These results reveal the impact of the Au substrate on the dielectric response of 2D monolayers with strong excitonic effect and will deepen our understanding of the 1L MoS2 –Au interaction. Abstract : Herein, the first spectroscopic ellipsometry study on a large‐area single‐crystalline monolayer MoS2 prepared by the emerging Au‐assisted mechanical exfoliation technique. In the dielectric function spectrum of the 1L MoS2 –Au hybrid system, it is observed that the A and B exciton peaks disappear. Further spectroscopic studies indicate that this is due to the interfacial charge transfer.